On‐Surface Synthesis of Porphyrin‐Complex Multi‐Block Co‐Oligomers by Defluorinative Coupling. Issue 3 (2nd December 2021) - Kawai, Shigeki; Ishikawa, Atsushi; Ishida, Shin‐ichiro; Yamakado, Takuya; Ma, Yujing; Sun, Kewei; Tateyama, Yoshitaka; Pawlak, Rémy; Meyer, Ernst; Saito, Shohei; Osuka, Atsuhiro
Abstract: On‐surface chemical reaction has become a very powerful technique to synthesize nanostructures by linking small molecules in the bottom‐up approach. Given the fact that most reactants are simultaneously activated at certain temperatures, a sequential reaction in a controlled way has remained challenging. Here, we present an on‐surface synthesis of multi‐block co‐oligomers from trifluoromethyl (CF3 ) substituted porphyrin metal complexes. The oligomerization on Au(111) is demonstrated with a combination of bond‐resolved scanning probe microscopy and density functional theory (DFT) calculations. Even after the first oligomerization of single monomer unit, the termini of the oligomer keep the CF3 group, which can be used as a reactant for further coupling in a sequential order. Consequently, copper, cobalt, and palladium complexes of bisanthracene‐fused porphyrin oligomers were linked with each other in a designed order. Abstract : A key for sequential on‐surface reaction: A coupling module of CF3 groups can react only when another reactant comes close enough. A combination of bond‐resolved scanning tunneling microscopy and DFT‐based ab initio molecular dynamics calculations allowed us to investigate the properties of the products and the reaction mechanism.